The association between alcohol consumption, cardiac biomarkers, left atrial size and re-ablation in patients with atrial fibrillation referred for catheter ablation - Barmano, Neshro (PLoS One, 2019)
BACKGROUND: Information on alcohol consumption in patients undergoing radiofrequency ablation (RFA) of atrial fibrillation (AF) is often limited by the reliance on self-reports. The aim of this study was to describe the long-term alcohol consumption, measured as ethyl glucuronide in hair (hEtG), in patients undergoing RFA due to AF, and to examine potential associations with cardiac biomarkers, left atrial size and re-ablation within one year after the initial RFA. METHODS: The amount of hEtG was measured in patients referred for RFA, and a cut-off of 7 pg/mg was used. N-terminal pro B-type natriuretic peptide (NT-proBNP) and the mid-regional fragment of pro atrial natriuretic peptide (MR-proANP) were examined and maximum left atrium volume index (LAVI) was measured. The number of re-ablations was examined up to one year after the initial RFA. Analyses were stratified by gender, and adjusted for age, systolic blood pressure, body mass index, presence of heart failure and heart rhythm for analyses regarding NT-proBNP, MR-proANP and LAVI and heart rhythm being replaced by type of AF for analyses regarding re-ablation. RESULTS: In total, 192 patients were included in the study. Median (25th– 75(th) percentile) NT-proBNP in men with hEtG ≥ 7 vs. < 7 pg/mg was 250 (96–695) vs. 130 (49–346) pg/ml (p = 0.010), and in women it was 230 (125–480) vs. 230 (125–910) pg/ml (p = 0.810). Median MR-proANP in men with hEtG ≥ 7 vs. < 7 pg/mg was 142 (100–224) vs. 117 (83–179) pmol/l (p = 0.120) and in women it was 139 (112–206) vs. 153 (93–249) pmol/l (p = 0.965). The median of maximum LAVI was 30.1 (26.7–33.9) vs. 25.8 (21.4–32.0) ml/m(2) (p = 0.017) in men, and 25.0 (18.9–29.6) vs. 25.7 (21.7–34.6) ml/m(2) (p = 0.438) in women, with hEtG ≥ 7 vs. < 7 pg/ml, respectively. Adjusted analyses showed similar results, except for MR-proANP turning out significant in men with hEtG ≥ 7 vs. < 7 pg/mg (p = 0.047). The odds ratio of having a re-ablation was 3.5 (95% CI 1.3–9.6, p = 0.017) in men with hEtG ≥ 7 vs. < 7 pg/mg, while there was no significant difference in women. CONCLUSIONS: In male patients with AF and hEtG ≥ 7 pg/mg, NT-proBNP and MR-proANP were higher, LA volumes larger, and there was a higher rate of re-ablations, as compared to men with hEtG < 7 pg/mg. This implies that men with an alcohol consumption corresponding to an hEtG-value ≥ 7, have a higher risk for LA remodelling that could potentially lead to a deterioration of the AF situation.